2005
DOI: 10.1128/aac.49.3.1093-1100.2005
|View full text |Cite
|
Sign up to set email alerts
|

Simocyclinone D8, an Inhibitor of DNA Gyrase with a Novel Mode of Action

Abstract: We have characterized the interaction of a new class of antibiotics, simocyclinones, with bacterial DNA gyrase. Even though their structures include an aminocoumarin moiety, a key feature of novobiocin, coumermycin A 1 , and clorobiocin, which also target gyrase, simocyclinones behave strikingly differently from these compounds. Simocyclinone D8 is a potent inhibitor of gyrase supercoiling, with a 50% inhibitory concentration lower than that of novobiocin. However, it does not competitively inhibit the DNA-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 47 publications
5
101
0
2
Order By: Relevance
“…It has been reported that simocyclinone D8 and GyrI prevent the binding of DNA to DNA gyrase (3,5). However, these compounds inhibit DNA gyrase but not, or only slightly, topo IV.…”
Section: Es-1273 Is a Type II Topoisomerase Specific Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that simocyclinone D8 and GyrI prevent the binding of DNA to DNA gyrase (3,5). However, these compounds inhibit DNA gyrase but not, or only slightly, topo IV.…”
Section: Es-1273 Is a Type II Topoisomerase Specific Inhibitormentioning
confidence: 99%
“…Other gyrase inhibitors include cyclothialidine (27), simocyclinone D8 (5), and three proteinaceous inhibitors, CcdB (4), microcin B17 (13), and GyrI (17). Their modes of action have been reported as follows: cyclothialidine inhibits ATPase activity of DNA gyrase B subunit (16), simocyclinone D8 and GyrI prevent the binding of DNA to DNA gyrase (3,5), and CcdB and microcin B17 stabilize DNA gyrase-DNA covalent complexes (1,25).…”
mentioning
confidence: 99%
“…Simocyclinone D8 is a structurally complex inhibitor of DNA gyrase (87,88). The final molecule is composed of four parts: an angucyclic polyketide, a D-olivose sugar, a tetraene linker, and an aminocoumarin moiety.…”
Section: Tfrs Regulating Self-resistance In Antibiotic-producing Orgamentioning
confidence: 99%
“…The genomics provide many molecular targets to be identified and effectively screened: 5,96) peptide deformylase (PDF), 109) aminoacyl-tRNA synthetase, 110) fatty acid biosynthesis, 111) isoprenoid biosynthesis, 112) lipid A biosynthesis, 113) efflux pump, 114) aromatic amino acid biosynthesis, 96) DNA replication (GyrB subunit inhibitor), 115) protein secretion, 116) cell wall biosynthesis (sortase), 117) proteasome, 118) glyoxylate cycle, 119) and signal networks (two-component systems and quorum sensing pathways). 120,121) 1.…”
Section: New Targetsmentioning
confidence: 99%